1992
DOI: 10.2165/00003088-199223060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Determining Plasma and Tissue Binding of Drugs

Abstract: The available techniques for the investigation of drug binding to plasma and tissues protein are reviewed and the advantages and disadvantages of the various techniques stated. A comparison of different plasma protein binding techniques is made which shows that the size of the unbound fraction of drug may be influenced by the method used. Protein binding may be assayed by methods including equilibrium dialysis, ultrafiltration, ultracentrifugation, gel filtration, binding to albumin microspheres and circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
122
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(122 citation statements)
references
References 161 publications
0
122
0
Order By: Relevance
“…Differences in plasma protein binding of a drug between species or individuals have an impact on pharmacokinetics and can influence the pharmacological activity [12,13]. For imatinib elevated levels of AGP have been related to in vivo resistance in mouse [9] and humans [14,15], whereas other investigators did not observe any relevant binding of imatinib to AGP employing fluorescence quenching [16].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in plasma protein binding of a drug between species or individuals have an impact on pharmacokinetics and can influence the pharmacological activity [12,13]. For imatinib elevated levels of AGP have been related to in vivo resistance in mouse [9] and humans [14,15], whereas other investigators did not observe any relevant binding of imatinib to AGP employing fluorescence quenching [16].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of PF-04971729 to rat, dog, and human plasma proteins was determined using the equilibrium dialysis method (Pacifici and Viani, 1992) using cellulose membranes (HTDialysis, Gales Ferry, CT) with a molecular mass cutoff of 12 to 14 kDa. For plasma protein binding studies, plasma was fortified with PF-04971729 at concentrations of 2.3 and 23 M, which reflect a theoretical plasma concentration anticipated in humans and a multiple thereof to assess saturation of plasma protein binding.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been noted that during one passage through the brain, in many cases, more drug than "free drug" can penetrate through the blood-brain barrier (Spector, 2000). Similarly, the hepatic uptake of many lipophilic compounds is not necessarily restricted by protein binding (Kurz and Fichtl, 1983;Pacifici and Viani, 1992), and it has been found that the antifungal activity of itraconazole and ketoconazole is not diminished despite extensive binding albumin (Schäfer-Korting et al, 1995). In agreement, Tran et al (1997) have reported that the K i value of stiripentol obtained in microsomal studies is more consistent with total plasma concentration than unbound concentration.…”
mentioning
confidence: 99%